Electromagnetic-thermal-mechanical behaviors of a no-insulation double-pancake coil induced by a quench in the self field and the high field. (13th January 2021) - Liu, Donghui; Li, Dongke; Zhang, Weiwei; Yong, Huadong; Zhou, Youhe
Abstract: High-temperature superconducting double-pancake (DP) coils wound by the no-insulation (NI) approach have been proved to have a high thermal stability and a self-protecting ability. This paper mainly studies the effect of a quench of one pancake coil on the electromagnetic-thermal-mechanical behaviors of an NI DP coil in the self field and the high field. An electromagnetic-thermal coupling quench model is used to calculate the distributions of current, temperature and electromagnetic field in the coil, and then a three-dimensional homogeneous mechanical model is built to analyze the changes in strain and stress during a quench by considering the distributions of thermal strain and Lorentz force of the coil. The results indicate that the obvious increase in circumferential current and radial current density in the bottom pancake coil is induced by a quench of the top pancake coil due to the electromagnetic coupling effect in the self field and the high field, and that the DP coil still has a negative coil voltage during a quench in different fields. Although the bottom pancake coil has a large circumferential current, the mechanical deformation of the DP coil during a quench is mainly caused by the temperature rise in the self field. The thermal expansion of the top pancake coil has a remarkable effect on the mechanical behaviors of the bottom pancake coil. Moreover, the DP coil has the same temperature rise and mechanisms of bypass current in the self field and the high field. However, the mechanical deformation of the DP coil is based on the combined effects of temperature rise and Lorentz force in the high field. It can be found that the values of the hoop and axial stresses are affected by a large electromagnetic stress.